Construction in lettres parisiennes - histoires d’exil: the relationship with the french language of Nancy Huston - Xypas, Rosiane (Lettres Françaises, 2017)
As part of the teaching of Francophone Literature at university, we assume that making students reflect about their relationship with the French language through literary texts written by bilingual authors can help them overcome their conflicts of learning. The best way to help them would be by making them conscious of their way of seeing things. We believe that students may become aware of their approach to learning and change it, if necessary, towards identifying the situations of bilingualism lived by the character-narrator. Nancy Huston’s letters to Leila Sebbar present valuable pages on this topic. The reading of the chosen texts should result in the construction of a common thread to understand the literary bilingualism starting from the following questions: How is the language identity of the author created? What is her relationship with the French language?